2018
DOI: 10.1002/clc.22847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on survival after sudden cardiac arrest

Abstract: Background Although elevated body mass index (BMI) is a risk factor for cardiac disease, patients with elevated BMI have better survival in the context of severe illness, a phenomenon termed the “obesity paradox.” Hypothesis Higher BMI is associated with lower mortality in sudden cardiac arrest (SCA) survivors. Methods Data were collected on 1433 post‐SCA patients, discharged alive from the hospitals of the University of Pittsburgh Medical Center between 2002 and 2012. Of those, 1298 patients with documented B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“… 23 Similar results were observed in patients who experienced sudden cardiac arrest, wherein a higher BMI was associated with reduced mortality. 24 Higher BMI was also associated with lower mortality in cases of coronary artery disease, heart failure, and diabetes. 25 In general, obese patients have higher mortality; however, paradoxically, higher mortality is often observed in normal-weight patients compared with obese patients.…”
Section: Relationship Between Obesity and Cardiovascular Diseasementioning
confidence: 96%
“… 23 Similar results were observed in patients who experienced sudden cardiac arrest, wherein a higher BMI was associated with reduced mortality. 24 Higher BMI was also associated with lower mortality in cases of coronary artery disease, heart failure, and diabetes. 25 In general, obese patients have higher mortality; however, paradoxically, higher mortality is often observed in normal-weight patients compared with obese patients.…”
Section: Relationship Between Obesity and Cardiovascular Diseasementioning
confidence: 96%
“…Saba et al showed that higher BMI is associated with lower all-cause mortality in the survivor of sudden cardiac arrest, suggesting the obesity paradox also applies to the post-cardiac arrest population. 6 In contrast, a single-center trial by Breathett et al demonstrated BMI <30 compared with BMI ≥30 was associated with better survival post-hypothermia for cardiac arrest. 9 …”
Section: Discussionmentioning
confidence: 95%
“…There is an impression that obesity confers some survival advantages in heart failure and cardiac surgery. 4 6 , 12 This inverse correlation between BMI and mortality is known as the obesity paradox. Greater metabolic reserve, younger age, and better cardioprotective medical therapy to obese patients are some hypotheses postulated for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large registry, men had a higher survival rate and a better neurological outcome at hospital discharge than women [13]. As for other cardiovascular diseases, survival expectancy after CA might be higher in obese patients and smokers (often called obesity and smoking paradoxes) [14,15,16], even though these are known risk factors triggering this cardiovascular complication. The delay between cardiac arrest and return of spontaneous circulation (ROSC), as well as the subsequent extent of brain damage, are both strongly associated with a poor outcome [17].…”
Section: Outcome After Cardiac Arrestmentioning
confidence: 99%